Analisis Kesiapan Pelaku Umkm Dalam Menyusun Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro Kecil Dan Menengah Pada Umkm Di Kabupaten Gianyar - Komang Diah Ayu Parwati; I Made Endra Lesmana Putra (UNHI Press, 2022)
Performance is a result achieved by a person during the work process. This study was made to look at the factors that can cause the performance of supervisors to increase, namely Independence, Accountability and Professional Expertise. All employees from 29 LPDs who are active in Payangan District are used as the population of this study. In this study, a saturated sample was used to determine the number of samples until it was found that 96 respondents were used as research samples. In this study, it was proven that the supervisor's performance could increase if the independence, accountability and professional expertise were improved.